Low Temperature Sealing Process and Properties of Kovar Alloy to DM305 Electronic Glass - Zhenjiang Wang; Zeng Gao; Junlong Chu; Dechao Qiu; Jitai Niu (Metals, 2020)
The low temperature sealing of Kovar alloy to DM305 electronic glass was realized by using lead-free glass solder of the Bi2O3-ZnO-B2O3 system in atmospheric environment. The sealing process was optimized by pre-oxidation of Kovar alloy and low temperature founding of flake glass solder. The effects of sealing temperature and holding time on the properties of sealing joint were studied by means of X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), etc. The results showed that the pre-oxidized Kovar alloy and DM305 electronic glass were successfully sealed with flake glass solder at the sealing temperature of 500 °C for 20 min. Meanwhile, the joint interface had no pores, cracks, and other defects, the shear strength was 12.24 MPa, and the leakage rate of air tightness was 8 × 10−9 Pa·m3/s. During the sealing process, element Bi in glass solder diffused into the oxide layer of Kovar alloy and DM305 electronic glass about 1 μm, respectively.